Radial Variation of Microfibril Angle and Cell Wall Thickness in Eucalyptus camaldulensis Clones - Veenin, Teera; Siripatanadilok, Somkid; Tangjaipitak, Kusol; Fujita, Minoru; Nobuchi, Tadashi; Awano, Tatsuya (วารสารวนศาสตร์ไทย, 2022)
Five superior clones and seedling of Eucalyptus camaldulensis at Sakaew plantation site in the eastern part of Thailand were selected for determining radial variation of microfibril angle, cell wall thickness. Results revealed that microfibril angle across the radial gradient of every samples slightly decreased with fluctuation from pith to bark but on the other hand, cell wall thickness steadily increased from pith to bark. Secondly, the mean microfibril angle of all clones were smaller than seedling, it meant that the wood properties of clones were better than seedling. Thirdly, thinner cell wall and larger microfibril angle were found in the region of all samples which were near the pith than that near the bark.